A Historical and Theological Survey of the Person of Melchizedek in Genesis, Psalms, and Hebrews - Hyde, Japheth Elwin; Amurao, Julio Cordero (11th International Scholars Conference, 2019)
This biblical and theological survey concentrates on the significant theological implications of Melchizedek reflected in the books of Genesis, Psalms, and Hebrews. This mysterious name and personality speak of its importance and significance in sacred canon of Genesis, Psalms, and Hebrews. This paper focused on the analysis of the commonality and uniqueness of Melchizedek‟s role in every reference cited in the biblical books. Moses‟ mentions of Melchizedek in Genesis were considered in determining his historical background. David‟s assertions of Melchizedek in Psalms show connection between Melchizedek and Jesus. Moreover, Paul pointed Melchizedek in Hebrews in connection to the new order of priesthood of Jesus Christ. This study explained in some details the superiority of Melchizedek‟s priesthood over the Aaronic or Levitical priesthood, as well as the superiority of Christ‟s priesthood over both Melchizedek‟s and Aaron‟s priesthood. The findings presented in this study indicate that though Melchizedek is little mentioned of in Scripture, he was an important figure closely tied to the significance of priesthood in Scriptures in relation to human salvation. He serves as a type of Christ, one who resembles the Heavenly KingPriest.